Implications of Indonesian Banking Statistics June 2025 on Managerial Economic Decision-Making - Decmoon Destine; Romauli Manik; Ferry Ardiyanto; Wilson Rajagukguk (Indonesian Journal of Business Analytics, 2025)
This study analyzes the Indonesian Banking Statistics June 2025 to strengthen economic literacy and managerial decision-making competence. Employing a quantitative descriptive–verificative method with secondary data from the Financial Services Authority (OJK) analyzed using SPSS 26, the study examines six indicators—assets, third-party funds (TPF), interest rates, capital adequacy ratio (CAR), problem loans, and productive assets. The findings reveal that assets, TPF, interest rates, CAR, and productive assets significantly and positively influence managerial performance, while problem loans exert a negative effect. The model explains 73.8% of managerial variation, underscoring the strategic importance of data-driven decisions in enhancing financial stability, efficiency, and governance within Indonesia’s banking sector.